THE EVALUATION OF WHEN ENGLISH RINGS A BELL (REVISED EDITION): TEACHERS’ PERSPECTIVES - Eva Faujiah; Flora Debora Floris (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
This study was done to find out the teachers` opinions regarding the coursebook, When English Rings A Bell (revised edition), in terms of (1) the coursebook`s language content, (2) the presentation of English skills in the coursebook, and (3) the coursebook`s topic, subject content, and social values. The data of this study was the teachers` written and/or oral answers of the questions used as the evaluation guidelines as proposed by Cunningsworth (1995). The teachers stated that (a) the topics, (b) subjects content, and (c) social and cultural values presented in the coursebook were appropriate to the Indonesian people`s way of life by not differentiating in gender. In addition, although the book provided practices for all English skills, the book should include additional material to support them, for instance, recorded material on a cassette for listening practices. The book did not also include all language contents as proposed by Cuningsworth (1995).